المواطنة في القانون التوجيهي للتربية الوطنية رقم 08-04 لسنة 2008 - بن ققة, سعاد (Université de M'sila, 2017)
الملخص المواطنة هي مصدر قوة كل المجتمعات إن وجدت ضمن بناها من بينهم النظام التربوي، الذي يعمل على تشكيل الأفراد معتمدا في ذلك على وسائط مختلفة، من بين أبرزها التشريع المدرسي. في هذا المجال، سيقوم هذا المقال بالكشف عن المواطنة المتضمنة في القانون التوجيهي رقم 08-04 للتربية الوطنية، من خلال أربع أبعاد هي: تفعيل ثقافة السلم، الحفاظ على عناصر الهوية، ابراز واجبات الدولة تجاه الفرد من خلال المسار التربوي، المساواة ما بين الأفراد على الصعيد التربوي. Abstrac Citizenship is the source of strength of all societies, if any, within their structure, including the educational system, which works on the formation of individuals, relying on different modes, among them school legislation. In this area, this article will reveal the citizenship included in the National Education Law No. 08-04, through four dimensions: activating the culture of peace, preserving the elements of identity, highlighting the duties of the state towards the individual through the educational track, equality between individuals At the educational level.
Keywords: المواطنة ; القانون التوجيهي; للتربية الوطنية رقم 08-04 لسنة 2008